Repurposing Agricultural Policies and Support: Options to Transform Agriculture and Food Systems to Better Serve the Health of People, Economies and the Planet - Gautam, Madhur; Laborde Debucquet, David; Mamun, Abdullah; Martin, Will; Piñeiro, Valeria; Vos, Rob (2022)
Madhur Gautam, David Laborde, Abdullah Mamun, Will Martin, Valeria Piñeiro, Rob Vos POLICY SEMINAR Can agricultural policies deliver better value for money for people, the planet, and the economy? Co-Organized by IFPRI and World Bank Group FEB 2, 2022 - 9:30 TO 11:00AM EST